Cre recombinase-mediated site-specific recombination between plant chromosomes. - Qin, M (1994)
We report the use of the bacteriophage P1 Cre-lox system for generating conservative site-specific recombination between tobacco chromosomes. Two constructs, one containing a promoterless hygromycin-resistance gene preceded by a lox site (lox-hpt) and the other containing a cauliflower mosaic virus 35S promoter linked to a lox sequence and the cre coding region (35S-lox-cre), were introduced separately into tobacco plants. Crosses between plants harboring either construct produced plants with the two constructs situated on different chromosomes. Plants with recombination events were identified by selecting for hygromycin resistance, a phenotype expressed upon recombination. Molecular analysis showed that these recombination events occurred specifically at the lox sites and resulted in the reciprocal exchange of flanking host DNA. Progenies of these plants showed 67-100% cotransmission of the new transgenes, 35S-lox-hpt and lox-cre, consistent with the preferential cosegregation of translocated chromosomes. These results illustrate that site-specific recombination systems can be useful tools for the large-scale manipulation of eukaryotic chromosomes in vivo.